2001
DOI: 10.1097/00003246-200108000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postpyloric feeding on gastroesophageal regurgitation and pulmonary microaspiration: Results of a randomized controlled trial

Abstract: Feeding beyond the pylorus is associated with a significant reduction in gastroesophageal regurgitation and a trend toward less microaspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(139 citation statements)
references
References 31 publications
5
126
0
8
Order By: Relevance
“…10 Notwithstanding our disappointing clinical experiences with the technique of nasoduodenal enteral feeding, including in critically ill ICU patients, 10 there has subsequently been considerable interest in the technique of postpyloric enteral feeding in the ICU patient, particularly in respect of reducing the incidence of aspiration pneumonia. [13][14][15][16][17][18][19][20][21][22] In attempting to assess and compare the results of the 10 controlled studies, [13][14][15][16][17][18][19][20][21][22] one is forced to conclude that the term postpyloric almost certainly refers to nasoduodenal tube placement and that some authors may have been somewhat optimistic in thinking that they had achieved intrajejunal tube placement. Overall, the results of the studies have been conflicting, and no clear consensus on the efficacy of postpyloric feeding in reducing the incidence of aspiration pneumonia has been documented.…”
Section: 9mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Notwithstanding our disappointing clinical experiences with the technique of nasoduodenal enteral feeding, including in critically ill ICU patients, 10 there has subsequently been considerable interest in the technique of postpyloric enteral feeding in the ICU patient, particularly in respect of reducing the incidence of aspiration pneumonia. [13][14][15][16][17][18][19][20][21][22] In attempting to assess and compare the results of the 10 controlled studies, [13][14][15][16][17][18][19][20][21][22] one is forced to conclude that the term postpyloric almost certainly refers to nasoduodenal tube placement and that some authors may have been somewhat optimistic in thinking that they had achieved intrajejunal tube placement. Overall, the results of the studies have been conflicting, and no clear consensus on the efficacy of postpyloric feeding in reducing the incidence of aspiration pneumonia has been documented.…”
Section: 9mentioning
confidence: 99%
“…8,9,23,24 One possible reason for this is that there is a need to aspirate gastric contents during postpyloric feeding. It is unlikely that this was performed in the above studies, [13][14][15][16][17][18][19][20][21][22] as the available feeding tubes did not incorporate a gastric aspiration port.…”
Section: 9mentioning
confidence: 99%
“…Para lograrlo, es importante la monitorización intermitente de los residuos de contenido, los que impactarían en la incidencia de NAVM 19,20 . Por tanto, independientemente a usar la ubicación gástrica o post-pilórica de alimentación, este consenso considera importante el uso de cantidades moderadas de alimentación controlando la existencia de residuos para evitar la sobre-distensión abdominal (IIB).…”
Section: La Alimentación Enteral Fraccionada ¿Conlleva Un Menor Riesgunclassified
“…56 Diverting the level of EN infusion lower in the GI tract reduces gastroesophageal reflux and risk for aspiration, and may reduce the incidence of pneumonia. Using a radioisotope placed in the EN formula, Heyland 57 showed that reducing the level of infusion from the stomach down to the third portion of the duodenum significantly reduced reflux and aspiration. Whether or not this reduction in reflux and aspiration reduces pneumonia is not as clear.…”
Section: -52mentioning
confidence: 99%